THE URGENCY OF IMPLEMENTING ORGANIZATIONAL CHANGE DEVELOPMENT AND DIGITAL TRANSFORMATION TO ACCELERATE GLOBALIZATION OF SMALL MICRO ENTERPRISES FAKFAK DISTRICT - Abdul Salam Biarpruga; Pompong B. Setiadi; Sri Rahayu; Rifda Firanti (Jurnal Scientia, 2023)
Changing the behavior and perception of micro, small business actors and traders from conventional business patterns to businesses that use digital information technology should be easy to do because the use of gadgets has become commonplace in society. The research aims to determine the level of readiness of micro and small business actors in Fakfak district in welcoming business globalization. Descriptive research with a combination of qualitative and quantitative approaches. The research population is micro and small business actors engaged in processed products typical of Fakfak, with a sample size of 109 people. Data was obtained from in-depth interviews using questionnaires and assessment standards which were converted using weighting techniques. The presentation of the weighting results uses a gap analysis approach which is displayed in a compilation of spider web diagrams. Data processing uses the SPSS version 2.3 statistical approach. The research results show that the majority of business actors are ready to develop their business organizations towards digitalization, but do not yet have strong self-confidence to compete globally.